Medial Meniscus Allograft Transplantation: Bone Plug Technique With Anatomic Anterior and Posterior Horn Fixation - Giovanna Medina, M.D., Ph.D.; Chilan B.G. Leite, M.D., Ph.D.; Gergo Merkely, M.D., Ph.D.; Christian Lattermann, M.D. (Arthroscopy Techniques)
Meniscus preservation is crucial for avoiding cartilage degeneration after symptomatic meniscal tears. Despite efforts, meniscal repair procedures may fail, which requires a partial or total meniscectomy. Meniscus allograft transplantation (MAT) presents a viable solution, offering symptom alleviation, enhanced knee function, and potential osteoarthritis progression delay. Although MAT can address both lateral and medial compartments, medial MAT poses greater challenges as the result of its intricate attachments and limited mobility. The medial meniscus's unique anatomy, including attachments to the intermeniscal ligament, deep medial collateral ligament, capsule, and the anterior cruciate ligament, demands meticulous transplantation techniques. Refinements in surgical techniques are ongoing, emphasizing the importance of anatomical precision, particularly in positioning the anterior and posterior horns of the medial meniscus. Here, we present a bone plug technique for medial MAT, prioritizing the accurate anatomical attachment of the anterior horns of the allograft to improve surgical outcomes.